Pengaruh Kenaikan Harga Bahan Bakar Minyak terhadap Pemilihan Moda Transportasi (Studi Kasus: Perkotaan Yogyakarta) - Yuliani, Richa Dwi; Priyanto, Sigit; Utomo, Suryo Hapsoro Tri (Pusat Penelitian dan Pengembangan Masyarakat (P3M), Politeknik Negeri Padang, 2023)
The increase in world oil prices has led to changes in the price of fuel oil (BBM) in Indonesia. The fuel price change policy impacts various sectors, including the transportation sector. Transportation is one of the basic human needs for moving from one place to another. Various factors are taken into consideration by the community in choosing the mode of transportation to be used. This study aims to analyze the impact of changes in fuel prices on preferences for transportation modes in urban Yogyakarta and to see how people's behaviour changes in mobility. The analytical method used in this research is descriptive and crosstab analysis. Descriptive analysis was used to identify the respondents' characteristics, the journey's characteristics, and the effect of rising fuel prices. Crosstab analysis is used to see the relationship between the characteristics of respondents and the choice of transportation mode before and after the fuel price increase. The data collection method was carried out by distributing questionnaires to the people of Yogyakarta. The choice of transportation mode when fuel oil increases does not change much, whereas in the scenario of changing fuel prices, there is a significant increase. This can be seen from the decrease in car users when there is an increase in the price of fuel oil, while the probability of motorcycle users when the fuel price rises until the fuel price is Rp 12,000 continues to increase, while when the fuel price is Rp 14,000 switch to using public transportation modes, namely the Trans Jogja bus. When the price of fuel oil increases, the frequency of primary trips does not change, while the frequency of secondary trips changes. Transportation costs incurred have increased, and the fuel used has changed; from the first, Pertamax switched to pertalite